2023
DOI: 10.3390/insects14080671
|View full text |Cite
|
Sign up to set email alerts
|

Validamycin Inhibits the Synthesis and Metabolism of Trehalose and Chitin in the Oriental Fruit Fly, Bactrocera dorsalis (Hendel)

Abstract: The oriental fruit fly, Bactrocera dorsalis (Hendel), is a notorious invasive pest that has raised concerns worldwide. Validamycin has been demonstrated to be a very strong inhibitor against trehalase in a variety of organisms. However, whether validamycin can inhibit trehalase activity to suppress trehalose hydrolysis and affect any other relevant physiological pathways in B. dorsalis remains unknown. In this study, the effects of validamycin injection on the synthesis and metabolism of trehalose and chitin w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…However, it lacks activity against Aedes aegypti. , Halogenin acts as a competitive inhibition of TREs, and the dissociation of the enzyme–inhibitor complex is notably slow . Furthermore, numerous studies have confirmed that validamycin and validamycin A, exhibit similar inhibitory effects on Lepidoptera, Diptera, Hemiptera, Coleoptera, and other insects. ,, …”
Section: Discussionmentioning
confidence: 99%
“…However, it lacks activity against Aedes aegypti. , Halogenin acts as a competitive inhibition of TREs, and the dissociation of the enzyme–inhibitor complex is notably slow . Furthermore, numerous studies have confirmed that validamycin and validamycin A, exhibit similar inhibitory effects on Lepidoptera, Diptera, Hemiptera, Coleoptera, and other insects. ,, …”
Section: Discussionmentioning
confidence: 99%